Survei Infeksi Salmonella spp. pada Pasien Anjing dan Kucing di Klinik/Rumah Sakit Hewan Daerah Istimewa Yogyakarta - Kajang, Elphan Augusta; Nugroho, Widagdo Sri; Haryanto, Aris (Jurnal Sain Veteriner, 2024)
Salmonellosis is an infectious disease that is zoonotic and includes food borne disease. Salmonella spp. can also be found in pets so that it can be a source of transmission of Salmonellosis to humans. The purpose of this study was to determine the infection level of Salmonella spp. in dogs and cats in clinics/animal hospitals in the Special Region of Yogyakarta. A total of 250 rectal swabs from 83 dogs and 167 cats were taken in this study. Isolation and identification of Salmonella spp. using Xylose Lysine Deoxycholate (XLD), Triple Sugar Iron Agar (TSIA), and Lysine Iron Agar (LIA) media. The isolates were confirmed by Polymerase Chain Reaction (PCR)using a primer Forward primer (5'- GCT AAG TAT GAC ATT CCG GT -3') and reverse (5'- CCA AAG ACT ATC TGC GGA AT -3') eith targeting the STM2773 (IroB) gene. Information on the patient's medical history was obtained based on the anamnesis and questionnaire to the animal owner. Data analysis was descriptive statistics. A total of 32 isolates of Salmomella spp. obtained through conventional methods and as many as 30 samples (12%) confirmed Salmonella spp. using PCR. A total of 11 (13.25%) of 83 dogs and 19 (11.27%) of 167 cats were identified as positive for Salmonella spp. The results of this study indicated that 12% of pet animals in the Special Region of Yogyakarta were infected with Salmonella spp.